Adaptasi Psikologis dari Pekerja Menuju Peran Baru Pensiunan - Muhammad Ilyas Nasrullah; Rafli, Muhammad; Rizanty, Rahmadhania; Sahin, Arif (Journal Of Education Research and Inovative, 2025)
Retirement is a critical transition in late adulthood that significantly impacts one’s selfidentity and psychological wellbeing. This article aims to examine the process of psychological adaptation among retirees as they construct a new identity after leaving formal work roles, using a literature review approach. We analyzed empirical and theoretical studies published over the past ten years in both national and international journals. Our review reveals that the retirement transition affects individuals’ selfidentity, selfesteem, and social roles. Factors that facilitate positive adaptation include retirement preparedness, social support, engagement in meaningful activities, and the use of adaptive coping strategies. Conversely, lack of readiness for retirement and loss of work role can trigger stress, anxiety, and even depression. These findings underscore the importance of structured psychosocial interventions to support identity reconstruction during retirement. This article is expected to inform the development of policies and practices in developmental psychology aimed at enhancing the wellbeing of older adults.